1992
DOI: 10.1164/ajrccm/146.6.1535
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Exudation of Bulk Plasma at Allergen Challenge in Allergic Asthma

Abstract: This study examined plasma exudation into the bronchial lumen after allergen challenge. A novel low-trauma technique was developed to challenge and lavage a medium-sized lingular or middle lobe bronchus. Eleven subjects with challenge-assessed pollen-sensitive asthma were allocated to fiberbronchoscopy in the supine position. In the control bronchus 0.5 ml diluent was instilled. The bronchus was occluded proximally 3 min later by inflation of a balloon, and lavage was carried out twice with 25 ml saline. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 7 publications
2
40
1
Order By: Relevance
“…The finding of unchanged lavage albumin levels does not necessarily mean that the exposure does not lead to plasma exudation. Thus, it has been found that bronchial allergen challenge did not increase the lavage fluid concentration of albumin, although other inflammatory parameters, including fibrinogen concentration in lavage fluid, were increased [13]. In the present study, there is also a possibility that the BAL, performed 20 h after the exposure, is too late to detect any early, transitory albumin increase.…”
Section: Discussioncontrasting
confidence: 50%
“…The finding of unchanged lavage albumin levels does not necessarily mean that the exposure does not lead to plasma exudation. Thus, it has been found that bronchial allergen challenge did not increase the lavage fluid concentration of albumin, although other inflammatory parameters, including fibrinogen concentration in lavage fluid, were increased [13]. In the present study, there is also a possibility that the BAL, performed 20 h after the exposure, is too late to detect any early, transitory albumin increase.…”
Section: Discussioncontrasting
confidence: 50%
“…After histamine challenge of the human nose without disease, the 60-kDa albumin and the 700-kDa a 2 -macroglobulin have thus been demonstrated to move equally swiftly across all barriers that exist between the venular compartment and the mucosal surface (see [18] and unpublished observations). In line with these observations, the acute exudative response to allergen challenge in human bronchi may best be measured as luminal entry of the large proteins, such as fibrinogen [19] and a 2 -macroglobulin [20] (see also later). Owing to unknown degrees of dilution/concentration, the actual volume of the luminal plasma exudate cannot be assessed but it may not be great in comparison with watery secretions: about 1 ml of bulk plasma per hour may enter the nasal passage at a symptomproducing allergen challenge in subjects suffering from allergic rhinitis.…”
Section: Fig 2 (A)mentioning
confidence: 88%
“…Allergen challenge in subjects with allergic asthma produces both immediate and late-phase plasma exudative responses [19,20,51]. In sensitized guinea pigs, allergen challenge of the tracheal mucosa also produces dual plasma exudative responses [52].…”
Section: Plasma-derived Molecule Contribution To Mucosalmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten minutes after allergen provocation a marked swelling of the bronchial mucosa could be observed through the bronchoscope. This reaction has been attributed to increased vascular permeability [32] allowing immediate exudation of proteins with a molecular mass as large as 340 kDa [32]. Albumin, with a molecular mass of 69 kDa, which is slightly larger than that of sCD14 (48-54 kDa), is already present at baseline conditions and increases significantly immediately after allergen challenge [33].…”
Section: Discussionmentioning
confidence: 99%